Tasamuh dalam Komunikasi Antarbudaya Jawa dan Tionghoa pada Proses Khitbah - Rizky Faturahman; Edi Amin (Bahasa Indonesia, 2025)
Film as a medium of preaching is effective in conveying messages of togetherness, respect for differences, and harmonious life according to Islamic teachings. Bu Tejo Sowan Jakarta is one of the films that depicts diversity and intercultural conflict that occurs in society, especially in the Javanese and Chinese engagement or proposal process. This study aims to examine intercultural communication between Javanese and Chinese cultures and the obstacles that arise in the proposal process in the film. Using a descriptive qualitative approach and the theoretical framework of the Development Model of Intercultural Sensitivity, this study collected data through film observation, in-depth interviews with directors, and cultural observers. Analysis was carried out on scenes in the film that depict intercultural conflict occurring. The results of the study indicate that intercultural communication in this film leads to tolerance through several stages, although obstacles still arise, especially in the context of the proposal. This study confirms that although cultural differences can trigger conflict, through proper communication, harmonious relationships can be created, as seen in this film.